ISOLATION OF LACTIC ACID BACTERIA FROM VANAME SHRIMP (Litopenaeus vannamei) AND ITS ANTAGONISM TO PATHOGEN BACTERIA - Sufaidah, Siti Nur; Nursyirwani, Nursyirwani; Feliatra, Feliatra (Asian Journal of Aquatic Sciences, 2024)
Vaname shrimp is one of Indonesia's leading export species and is widely cultivated. The main problem in vaname shrimp pond cultivation is the attack of shrimp diseases caused by bacteria or viruses. This study aims to isolate and identify lactic acid bacteria (BAL) from vaname shrimp (Litopenaeus vannamei) and test their antagonism against pathogenic bacteria. The research was conducted from February to April 2023. The method used in this study is a survey method. Sampling was conducted at the vaname shrimp pond of the Fisheries Service Task Unit (UPT), Tanjung Punak Village, Rupat Utara District, Bengkalis Regency, Riau. The method used in this research was a survey method. BAL was isolated using MRS Agar + CaCO3 media. The Kirby-Bauer method was used to test bacterial antagonism against pathogenic bacteria. Based on the identification of seven isolates, it was found that only four isolates were positively identified as LAB bacteria, namely 47D, 54T1, 73DB1, and 73BD2. The results of the antagonism test against pathogenic bacteria showed that all BAL isolates could not suppress the growth of E. coli bacteria. However, these isolates suppressed the growth of A. hydrophila bacteria, with the widest inhibition zone diameter on isolate 54T1 (4.2 mm). On Vibrio sp. bacteria, the widest inhibition zone of BAL was on isolate 73DB1 (6 mm). These results indicate that the antibacterial activity produced by BAL is still relatively weak.